PRECISE MEASUREMENTS OF ATMOSPHERIC METHANE CONCENTRATION AT SYOWA STATION (69°00'S, 39°35'E), ANTARCTICA - アオキ, シュンジ; ナカザワ, タカキヨ; ムラヤマ, ショウヘイ; カワグチ, サダオ; AOKI, Shuhji; NAKAZAWA, Takakiyo; MURAYAMA, Shohei; KAWAGUCHI, Sadao (National Institute of Polar Research, 1992)
P(論文) Precise measurements of atmospheric CH_4 concentration was initiated at Syowa Station in February 1988. A regular diurnal variation is not observable but irregular variations are sometimes observed with extremely small amplitude of 5 ppbv at most. A seasonal variation is clearly seen with the amplitude of 30 ppbv. Annual mean values of CH_4 concentration are 1640 and 1651 ppbv for 1988 and 1989,respectively. departmental bulletin paper